Using Digital Resources in the Measure of the Impact of Working Memory on Students’ Acquisition of Mathematical Knowledge - Mamoun, B El; Erradi, M; Mhouti, A El (International Journal of Computer Sciences and Engineering, 2025)
Working Memory (WM) is the mental thinking space in which learners manipulate or act on aspects of their knowledge in mathematical learning situations. It is the activity that allows learners to create links between the data collected during such a situation, and the knowledge gained from long-term memory, to synthesize new knowledge in mathematics, and when they direct their learning and thinking activity to calculate or solve mathematical problems. This work investigates the impact of WM on the academic achievement of mathematics knowledge using electronic learning resources. It also attempts to determine the process of WM to foster and improve the cognitive structures of the learner to facilitate the transformation of information and to succeed in a learning mathematics session. The results obtained lead to a good correlation between these two variables. The digital resources used promote the expected results, and facilitate the collection and processing of the data needed for such research. This makes it possible to better understand the functioning of WM during a learning situation in mathematics, and thus to be able to lead to solutions when learning problems appear.